Considerations for acceptability in Bible translation - Chemorion, Diphus C. (Verbum et ecclesia, 2009)
The ministry of Bible translation is an important component of the Great Commission (Matthew 28:18-20) and its mandate is to reach everyone with the word of God. One of the main goals of a Bible translation project is to produce a translation that will be used by the church in a given language group. Bible translation teams believe that the lives of the intended recipients will be changed positively when they gain access to Scripture in their own language. However, recent developments regarding Scripture use have shown that the success of any Bible translation project depends on whether or not its products are acceptable. If a translation is not acceptable to the intended audience, it may not be used, and as a result, it may fail to bring about the desired impact. This article explores the concept of ‘acceptability’ as used in Bible translation and highlights important considerations that translators need to keep in mind in order to enhance the acceptability of their translation products.